Persistent hypersplenism following successful hematopoietic stem cell transplantation: unraveling the cellular components of extramedullary residual disease and donor hematopoiesis—a case report - Besiridou, Eleni; Bhatt, Osheen; Yurukova, Andrea; Sahu, Anshupa; Kinkley, Sarah; Fischer, Victoria; Triviai, Ioanna (Frontiers in Hematology, 2024)
In this study, we unveil an unprecedented case of graft failure following Hematopoietic Stem Cell Transplantation (HSCT) in a patient with a Myeloproliferative Neoplasm (MPN) who had achieved bone marrow (BM) remission. We outline the intricate cellular components of splenic hematopoiesis that derive from both the recipient and donor, underpinning the persistence of fibrosis. Our investigation characterizes distinct cellular populations that play a pivotal role in graft exhaustion and introduces an unusual hypothesis regarding the perpetuation of a malignant niche in extramedullary sites within the context of HSCT.